The Role of Career Path Management in Nurses’ Succession Planning - Abdolali Keshtegar (Journal of Global Pharma Technology, 2018)
Background and purpose: Nurses are ones of service organizations’ forces who are in direct contact with clients. So, they must have special mastery in their work. Therefore, nurses’ career path and process of their succession is very important. This research aimed to study the relationship between career path management and succession of nurses. Study method: The present research was descriptive-correlation. The present research’s statistical population included 280 nurses working in Iranshahr hospitals selected by census method as statistical sample and the questionnaires including succession Rothwell (2006) and career path management Delong (1982) were distributed among them. Formal validity was used to determine questionnaires validity and Cronbach’s alpha was used to determine reliability which was 0.84 for succession questionnaire and it was 0.85 for career path. Data was analyzed by Pearson correlation inferential test and simple regression in SPSS21software. Findings: The variables of career path management and succession were in a good position. At 99% significant level, correlation coefficient of career path management and succession and its dimensions including succession planning assessment, filing the educational vacancy, personal performance assessment, current work requirements and making a commitment to systematic succession planning) were 0.65, 0.784, 0.72, 0.682, 0.570, 0.178, -0.352 and -0.203, respectively. According to regression results, 42.3 percent of succession changes can be explained based on career path management. Conclusions: Career path management appropriately explains succession system. A more worthy succession system will be established through career path management. So, we will enjoy the existence of qualified nurses in positions by a special consideration to career path management.Keywords: Nurse, Succession, Career path management.